Interfacial Engineering of Binder‐Free Janus Separator with Ultra‐Thin Multifunctional Layer for Simultaneous Enhancement of Both Metallic Li Anode and Sulfur Cathode. Issue 28 (20th June 2022) - Wu, Shuanglin; Yao, Yingmei; Nie, Xiaolin; Yu, Zhifeng; Yu, Yanting; Huang, Fenglin
Abstract: Exploring a scalable strategy to fabricate a multifunctional separator is of great significance to overcome the challenges of lithium polysulfides (LiPSs) and dendritic growth in lithium‐sulfur batteries (LSBs). Herein, a binder‐free Janus separator is constructed by interfacial engineering. At the cathode interface, an ultra‐thin covalent triazine piperazine film containing tailorable micropores and adsorption sites is decorated on polyacrylonitrile (PAN) membrane by in situ interfacial polymerization, building a triple barrier for LiPSs. The combination of steric hindrance and chemical adsorption reduces LiPS's migration by 81.85%. Meanwhile, at the anode interface, a fast‐ionic conductor Li6.4 La3 Zr1.4 Ta0.6 O12  (LLZTO) is created on the surface of PAN nanofiber by magnetron sputtering to suppress dendrite growth. Even though there is no binder between the ceramic layer and the fibrous separator, sputtering creates an inter‐embedded structure that ensures no depowering after cycling. Furthermore, the PAN‐based separator displays a high temperature tolerance of 180 °C. Consequently, the cell delivers a high capacity of 1287.9 mAh g −1 at 0.5 C and stable cycling performance with an ultra‐low capacity decay rate of 0.059% per cycle over 500 cycles. This work provides a scalable strategy for functionalizing separators to tackle the challenges in LSBs, which is binder‐free, stripping‐free, and essentially thickening‐free. Abstract : A binder‐free Janus separator is constructed by a scalable strategy. The ultra‐thin covalent triazine piperazine film with tailorable micropores and chemical adsorption sites decorated on the polyacrylonitrile (PAN) nanofibrous separator creates a three‐fold barrier for lithium polysulfides. Li6.4 La3 Zr1.4 Ta0.6 O12 on the surface of PAN nanofiber created by magnetron sputtering ensuring the stability of Li anode.